A regression model of hip flexion force of the dominant leg among Malaysian adults in standing posture - Halim, Isa; Mahadzir, Muhammad Nadzirul Izzat; Abdullah, Zulkeflee; Mafazi, Nurul Wirdah; Kasim, Mohd Shahir; Saptari, Adi (Universiti Putra Malaysia Press, 2025)
Introduction: The disregard for hip flexion force when designing foot-operated equipment poses a potential threat to non-compliance with ergonomics principles, ultimately impacting occupational health. Nevertheless, there is a noticeable lack of studies focusing on the hip flexion strength of Malaysian adults in a standing position. This paper aimed to measure the maximum force of hip flexion strength and formulate a regression model for Malaysian young adults in a standing posture. Materials and methods: The experiment invited sixty Malaysian adults aged 20 to 26 years old. A digital force gauge (Mark-10, USA) was used to measure the hip flexion force. A regression model was developed to determine the influence of gender, body mass, body height, thigh length, and thigh circumference on the hip flexion force. Results: The results of this study found that the means of hip flexion force for the male and female participants were 192.8 N and 126.0 N, respectively. The regression model concluded that gender is the most significant factor influencing hip flexion force (p<0.01). The body mass, body height, thigh length, and thigh circumference positively correlate to hip flexion force. However, these correlations were not statistically significant (p>0.05). Conclusion: This study concluded that the relationship between anthropometric parameters and hip flexion force is not always straightforward and can be influenced by various factors. To gain a more comprehensive picture of hip flexion, it is essential to consider other potential factors such as muscle mass, neuromuscular control, and joint mechanics.